D’allié à ennemi. Stéréotypes et représentations du combattant russe dans les magazines illustrés français durant la Grande Guerre - Raymond Blanchard; Joceline Chabot; Sylvia Kasparian (Amnis)
Recent research in the social and cultural history of the Great War views literary, media, and iconographic productions as a significant aspect of the individual and collective war experience, and scholars see these productions as forming « war cultures ». Historians analyze these « war cultures » partly through the press, which position at the crossroads of government propaganda and public opinion makes it an effective tool for understanding popular mobilization in the context of a total war. Through an interdisciplinary approach, this article aims to identify the stereotypes that governed representations of the Russian ally in the French illustrated press during the Great War. Specifically, we examine the evolution the representations of the Russian combatant during the Great War, in order to determine the extent to which there was rupture or continuity within these representations, as the historical context evolved from 1914 to 1919.